Exact Solutions of Accelerated Flows for a Generalized Burgers' Fluid, I: The Case - Khan, Ilyas; Abid, Hussanan; Mohd Zuki, Salleh; Razman, Mat Tahar (Science and Knowledge Research Society, 2016)
An analysis is presented to develop the exact solutions for the accelerated flows of a generalized Burgers' fluid when the relaxation time satisfying the condition 2 /4   . The corresponding expressions for the velocity field and associated tangential stress are obtained by using Laplace transform for the problems of flow induced by constantly accelerated plate. The obtained solutions are presented through simple or multiple integrals in terms of Bessel functions. The corresponding solutions for Burgers' fluid are recovered as special case of the solutions obtained here.